Case Report: Baricitinib improved alopecia areata in a pediatric patient with atopic dermatitis - Wang, Sihan; Xu, Ziqian; Zhu, Xiaoxia; Fan, Xin; Yu, Yingzhe; Lin, Bingjiang; Xu, Suling (Frontiers in Pediatrics, 2025)
Alopecia areata (AA) is a common non-scarring hair loss condition whose specific pathogenesis is not yet fully understood. In children, AA often co-occurs with atopic dermatitis (AD), complicating treatment. Here, we report the case of a child with myasthenia gravis who had severe AA and moderate AD. The child had previously been treated with local injections of corticosteroids and developed total hair loss and AD after discontinuing corticosteroid use. After approximately one year of treatment with baricitinib, 4 mg once daily, combined with twice-daily application of a corticosteroid ointment, a significant improvement in the child's condition was observed, with the Severity of Alopecia Tool score dropping from 100 to 24.4 and Eczema Area Severity Index score to 0. New vellus hairs were clearly observable under trichoscopy, which contrasted significantly with the pre-treatment state. Throughout the treatment process, the patient's clinical symptoms, blood cell counts, liver and kidney function, and coagulation functions were essentially normal, with no significant adverse reactions observed except for folliculitis on the scalp. We discuss common targets in the pathogenesis of AA and AD as well as the safety and prospects of Janus kinase inhibitors for the treatment of pediatric patients with these conditions.